The case for centralized federalism - DiGiacomo, Gordon; Flumian, Maryantonett (Governance series (Ottawa, Ont.), 2010)
Features an array of experts who condemn the federal government's submissiveness in its dealings with the provinces and calls for a renewed federal assertiveness. In this book, they argue that the federal government is best placed to create effective policy, support democracy and respond to issues of national importance.